Writing the short film. - Cooper, Pat, ....-; Dancyger, Ken, ....- (Amsterdam : Elsevier, 2005)
Part 1: Storytelling in General; Telling a Story in Images; Using Sound to Tell the Story; Finding a Main Character for Your Story; Writing an Original Short Screenplay; Rewriting Your Script Part 2: Storytelling Strategies; Visualization Strategies; Dramatic Strategies; Characterization Strategies; Dialogue Strategies; Part 3: The Melodrama; The Docudrama; Hyperdrama; Experimental Drama; Part 4: New Directions; A Redefined Future; Appendix: Short Screenplays
Keywords: Filmscenario's.; Schrijven -- Scenario's.